Archival research in historical organisation studies : theorising silences - Durepos, Gabrielle; Thurlow, Amy (Critical management studies (Series), 2025)
Archival Research in Historical Organisation Studies: Theorising Silences offers an accessible account of theorising the archive, contesting the narrow definitions of the archive with a view beyond a mere repository of documents. Offering an accessible theorised discussion of business archives that surfaces populations that have been marginalised in the archive, Archival Research in Historical Organisation Studies gives voice to marginalised populations. Outlining the processes that have led to previous exclusions from business archives, Durepos and Thurlow seek to redress these absences and contribute to a better future. The Critical Management Studies series both contains and seeks a range of contributions aimed at far-reaching socio-political change, from those who self-identify as CMS scholars, critical scholars of management, or no particular identity project.